Lietuviešu valodas ietekme uz skolēnu vācu valodas kompetenci - Raudiene, Lina (Latvijas Universitāte, 2010)
Bakalaura darba tēma ir „Lietuviešu valodas ietekme uz skolēnu vācu valodas kompetenci“. Darba uzdevums ir noskaidrot, kā dzimtā – lietuviešu - valodā ietekmē skolēnu vācu valodas kompetenci dažādos valodas līmeņos. Liela nozīme svešvalodu apgūšanā ir interferences parādībām, kas pārsvarā un visbiežāk ir kļūdu avots svešvalodā. Šajā bakalaura darbā tiek pētīti lietuviešu valodas interferences veidi un to izpausme skolēnu vācu valodā. Empīriskais materiāls ir iegūts, strādājot par vācu valodas skolotāju. Darba gaitā iegūtās atziņas palīdzēs optimizēt vacu valodas pasniegšanu Lietuvas skolās.

There are many different languages in the world. All languages are very beautiful and unique. Every person speaks in his own native language. But it is very important to know, speak and understand several foreign languages. My bachelor paper work’s theme is “The Influence of Lithuanian on Primary school student’s Linguistic competence“. This theme is very relevant to me, because I work at school as a teacher of German. I am interested in the merits and demerits of Lithuanian students, who study German. The aim and objectives of this work is to clarify what helps Lithuanian native speakers to learn German as a foreign language. What problems and difficulties are encountered? What is the motivation of Lithuanian students to learn German? How does their native language influence the learning of German? It is clear that when learning a foreign language the connection with native tongue is kept. Teachers should be concerned about the improvement of students, teaching not only a foreign language, but perfecting speaking, writing, reading and listening skills of the native language as well.
Influence of Lithuanian on the Linguistic Competence of Primary School Students
Keywords: Vācu filoloģija